SCIENTIFIC AND TECHNICAL INFORMATION AS THE BASIS FOR SUCCESSFUL DEVELOPMENT OF INNOVATIVE ACTIVITY OF THE SUBJECTS OF ECONOMIC REAL SECTOR IN BELARUS - R. N. Sukhorukova (Informatika)
The problems of creation and forming information resources on science and technology, the impact of information on the process of providing enterprises and organizations of Belarus with scientific and technical information are considered. Specific examples are given. Actual problems and tasks are identified.